Number of Virus Particles in Insects and Plants Infected with Wound Tumor Virus - Streissle, Gert (1968)
A new procedure for counting virus particles was employed to measure the concentration of wound tumor virus in purified virus preparations, in plant tumors, and in the insect vector. Partially purified wound tumor virus was used to establish the quantitative features of the method. A 1-g amount of plant tumor tissue contained an average of 5 × 10(10) virus particles and 1 g of insect tissue contained 2 × 10(10) particles.